2020
DOI: 10.1089/aut.2019.0044
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Evaluation of the Anxiety Scale for Autism-Adults

Abstract: Background: Anxiety is highly prevalent in autistic adults and can cause a significant impact on functioning and quality of life. There are no existing measures of anxiety designed and validated specifically for autistic adults. In this study, we aimed to adapt an existing anxiety measure designed for autistic children, in collaboration with autistic adults and other professionals, to make it suitable for use for autistic adults and to examine the measurement properties of the newly designed measure. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…36,37 While their methods may differ from ours, like us, they found that the existing measure did not fully capture the intended construct, so they worked with autistic adults to create additional items. Similarly, Rodgers et al 65 consulted with autistic adults to adapt an anxiety scale to be more accessible to this population. Moreover, research teams have used participatory approaches to create new instruments on topics such as autistic adults' vulnerability to negative life experiences.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 While their methods may differ from ours, like us, they found that the existing measure did not fully capture the intended construct, so they worked with autistic adults to create additional items. Similarly, Rodgers et al 65 consulted with autistic adults to adapt an anxiety scale to be more accessible to this population. Moreover, research teams have used participatory approaches to create new instruments on topics such as autistic adults' vulnerability to negative life experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Each item is rated on a scale from "Never" (0) -"Always" (3), with total scores ranging from 0-60. Scores at or above 28 indicate clinically signi cant levels of [35]. The ASA-A has strong evidence in support of its measurement properties (factor structure, internal consistency, test re-test reliability, convergent and divergent validity) in autistic adults [35].…”
Section: Anxiety Scale For Autism (Adults) (Asa-a)mentioning
confidence: 95%
“…Scores at or above 28 indicate clinically signi cant levels of [35]. The ASA-A has strong evidence in support of its measurement properties (factor structure, internal consistency, test re-test reliability, convergent and divergent validity) in autistic adults [35]. Cronbach's alpha for whole scale: Autistic group a=.921, possibly autistic group a=.926, non-autistic group a=.943.…”
Section: Anxiety Scale For Autism (Adults) (Asa-a)mentioning
confidence: 97%
See 1 more Smart Citation
“…Social Responsiveness Scale (SRS-2; [53]: the SRS-2 is a standardised self-report questionnaire used extensively to rate the social communication difficulties of autistic adults and children. Estimates of internal consistency of between .94 to .96 have been reported whilst the predictive validity of the adult form found a specificity level of .60 and sensitivity of .86 [54] Anxiety Scale for Autism-Adult (ASA-A©; [55]): the ASA-A© is a 20-item self-report measure designed to measure anxiety in autistic adults. It consists of four subscales: Social Phobia (SP), Anxious Arousal (AA) and Uncertainty (U).…”
Section: Baseline Characterisationmentioning
confidence: 99%